Altering the availability or proximity of food, alcohol, and tobacco products to change their selection and consumption - Hollands, Gareth J (Cochrane Database Syst Rev, 2019)
BACKGROUND: Overconsumption of food, alcohol, and tobacco products increases the risk of non‐communicable diseases. Interventions to change characteristics of physical micro‐environments where people may select or consume these products ‐ including shops, restaurants, workplaces, and schools – are of considerable public health policy and research interest. This review addresses two types of intervention within such environments: altering the availability (the range and/or amount of options) of these products, or their proximity (the distance at which they are positioned) to potential consumers. OBJECTIVES: 1. To assess the impact on selection and consumption of altering the availability or proximity of (a) food (including non‐alcoholic beverages), (b) alcohol, and (c) tobacco products. 2. To assess the extent to which the impact of these interventions is modified by characteristics of: i. studies, ii. interventions, and iii. participants. SEARCH METHODS: We searched CENTRAL, MEDLINE, Embase, PsycINFO, and seven other published or grey literature databases, as well as trial registries and key websites, up to 23 July 2018, followed by citation searches. SELECTION CRITERIA: We included randomised controlled trials with between‐participants (parallel group) or within‐participants (cross‐over) designs. Eligible studies compared effects of exposure to at least two different levels of availability of a product or its proximity, and included a measure of selection or consumption of the manipulated product. DATA COLLECTION AND ANALYSIS: We used a novel semi‐automated screening workflow and applied standard Cochrane methods to select eligible studies, collect data, and assess risk of bias. In separate analyses for availability interventions and proximity interventions, we combined results using random‐effects meta‐analysis and meta‐regression models to estimate summary effect sizes (as standardised mean differences (SMDs)) and to investigate associations between summary effect sizes and selected study, intervention, or participant characteristics. We rated the certainty of evidence for each outcome using GRADE. MAIN RESULTS: We included 24 studies, with the majority (20/24) giving concerns about risk of bias. All of the included studies investigated food products; none investigated alcohol or tobacco. The majority were conducted in laboratory settings (14/24), with adult participants (17/24), and used between‐participants designs (19/24). All studies were conducted in high‐income countries, predominantly in the USA (14/24). Six studies investigated availability interventions, of which two changed the absolute number of different options available, and four altered the relative proportion of less‐healthy (to healthier) options. Most studies (4/6) manipulated snack foods or drinks. For selection outcomes, meta‐analysis of three comparisons from three studies (n = 154) found that exposure to fewer options resulted in a large reduction in selection of the targeted food(s): SMD −1.13 (95% confidence interval (CI) −1.90 to −0.37) (low certainty evidence). For consumption outcomes, meta‐analysis of three comparisons from two studies (n = 150) found that exposure to fewer options resulted in a moderate reduction in consumption of those foods, but with considerable uncertainty: SMD −0.55 (95% CI −1.27 to 0.18) (low certainty evidence). Eighteen studies investigated proximity interventions. Most (14/18) changed the distance at which a snack food or drink was placed from the participants, whilst four studies changed the order of meal components encountered along a line. For selection outcomes, only one study with one comparison (n = 41) was identified, which found that food placed farther away resulted in a moderate reduction in its selection: SMD −0.65 (95% CI −1.29 to −0.01) (very low certainty evidence). For consumption outcomes, meta‐analysis of 15 comparisons from 12 studies (n = 1098) found that exposure to food placed farther away resulted in a moderate reduction in its consumption: SMD −0.60 (95% CI −0.84 to −0.36) (low certainty evidence). Meta‐regression analyses indicated that this effect was greater: the farther away the product was placed; when only the targeted product(s) was available; when participants were of low deprivation status; and when the study was at high risk of bias. AUTHORS' CONCLUSIONS: The current evidence suggests that changing the number of available food options or altering the positioning of foods could contribute to meaningful changes in behaviour, justifying policy actions to promote such changes within food environments. However, the certainty of this evidence as assessed by GRADE is low or very low. To enable more certain and generalisable conclusions about these potentially important effects, further research is warranted in real‐world settings, intervening across a wider range of foods ‐ as well as alcohol and tobacco products ‐ and over sustained time periods.